Report on the International Symposium on Low Vision - Brisbin, Scott (Canadian Journal of Optometry, 2021)
The International Symposium on Low Vision held at the School of Optometry, University of Waterloo, June 25th to 27th was a major event in Canadian Optometry. It was the first of its type ever held but, no doubt, it will not be the last. The rapidly rising demand for low vision services will ensure that.